THE PROFILE OF STUDENTS’ PSYCHOLOGICAL WELL-BEING AT THE FACULTY OF TARBIYAH AND TEACHER SCIENCES SALATIGA STATE ISLAMIC INSTITUTE - Mulawarman, Mulawarman; Antika, Eni Rindi; Hariyadi, Sigit; Prabawa, Abi Faizzarahman; Arinata, Firdian Setiya; Wibowo, Ari Eko; Niswah, Nilna Aula; Tsani, Yasmin Meilana; Mulyawati, Vira (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
The state of students' psychological well-being has an impact on their mental health. In this study, the psychological well-being of students at the Faculty of Tarbiyah and Teaching Science (FTTS) at Salatiga State Islamic Institute. This study used a cross-sectional survey design and a descriptive quantitative methodology. The study's subjects were 142 students at FTTS, Salatiga State Islamic Institute, who were chosen using a simple random sampling process. The psychological well-being scale used in this study is an adaptation of Riff's Well-Being Scale. Based on the instrument's validity and reliability tests, the instrument's reliability (r) score was 0.867, and the r count validity score ranged from 0.231 to 0.652. These findings show that the instrument is reliable and valid. The IBM SPSS program was used for data analysis. The findings indicated that students at FTTS, Salatiga State Islamic Institute are generally categorized as moderate for their psychological well-being, and according to the t-test (p= 0.090 > 0.05), there is no statistically significant difference between the psychological well-being of male and female students. According to the study's findings, students' psychological well-being can be enhanced by using a variety of services, including counseling and mindfulness therapy provided by counselors.